Children in Boxing and Martial Arts Should Be Better Guarded From Facial Injuries. Issue 2 (June 2022) - Gotlieb, Rachael J.; Sorenson, Thomas J.; Borad, Vedant; Schubert, Warren
Study Design: Cross-sectional study Objective: Childhood participation in boxing and martial arts has increased over the past decade, and these activities are well-known causes of traumatic injury. We hypothesized that the face is frequently injured in the setting of pediatric boxing and martial arts trauma in the United States and that there are identifiable injury patterns. Methods: We performed a cross-sectional study of consecutive pediatric patients in the National Electronic Injury Surveillance System (NEISS) from January 1, 2010 to December 31, 2019. Patients were included in our study if they were younger than 18 years of age and evaluated in the emergency department (ED) after boxing or martial arts trauma. Primary outcome was facial injury. Other variables of interest include age, sex, ED disposition, type and location of injury. Descriptive and univariate statistics of the primary outcome were computed with these variables. Results: There were 4, 978 total pediatric patients injured due to boxing and martial arts trauma reported by NEISS-participating EDs during the study period, and 264 patients experienced injury to the face (264/4978; 5.3%). Over 20% (n = 60) of reported facial injuries were fractures; the most fractured structure was the nose (42/60; 70), orbit (11/60; 18.3%), and mandible (6/60; 10%). Almost 20% (11/60%) of pediatric facial fractures due to boxing and martial arts trauma involved fighting a family member or friend, and a punch was the most common mode of fracture (42/58; 72.4%). Conclusions: Facial injuries comprise about 5% of injuries after boxing and martial arts trauma and 22% of these facial injuries are fractures. If children choose to participate, parents, coaches, trainers, officials, and community leaders should make the greatest effort possible to minimize risk, including the mandatory use of head and face protective gear and elimination of training fighting, or "sparring."